Pengaruh Gaya Kepemimpinan Terhadap Kinerja Pegawai Pada PT. PLN UP3 Kota Gorontalo - Anggriani Husain (Anthronomics: Jurnal Manajemen Sumber Daya Manusia, 2025)
This study aims to determine the influence of transactional and transformational leadership styles on Employee Performance (Y) at PT. PLN Gorontalo City Customer Service Implementation Unit (UP3). The method used in this study is through a quantitative approach with a descriptive presentation. The population determination and sampling techniques used in this study were the census method, the data collection techniques used were observation, interviews, questionnaires, and documentation, and the analysis method used was the path analysis method (Path Analysis). The results of the first test showed that the variables of transactional leadership style (X1) and transformational leadership style (X2) simultaneously had a significant effect on Employee Performance (Y) at PT. The PLN Customer Service Implementation Unit (UP3) in Gorontalo City is 0.415, or 41.5%. The results of the second hypothesis test indicate that the transactional leadership style (X1) partially affects employee performance at PT. PLN Customer Service Implementation Unit (UP3) Gorontalo City is 0.480 or 480%. The results of the third test show that transformational leadership style (X2) partially affects employee performance at PT. PLN Customer Service Implementation Unit (UP3) Gorontalo City is 0.238 or 23.8%.